1996
DOI: 10.1111/j.1365-2885.1996.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inflammation on the disposition of phenylbutazone in Thoroughbred horses

Abstract: The effect of inflammation on the disposition of phenylbutazone (PBZ) was investigated in Thoroughbred horses. An initial study (n = 5) in which PBZ (8.8 mg/kg) was injected intravenously twice, 5 weeks apart, suggested that the administration of PBZ would not affect the plasma kinetics of a subsequent dose. Two other groups of horses were given PBZ at either 8.8 mg/kg (n = 5) or 4.4 mg/kg (n = 4). Soft tissue inflammation was then induced by the injection of Freud's adjuvant and the administration of PBZ was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(13 reference statements)
0
8
0
1
Order By: Relevance
“…Step 2 -computation of EPC: PBZ plasma clearance has been measured by many authors; mean reported values range from 16.3 to 41.3 ml/kg/h (Soma et al 1983;Lees et al 1987;Mills et al 1996). The most conservative value is obtained by taking the highest clearance value, i.e.…”
Section: An Example: Computational Steps For the Determination Of An mentioning
confidence: 99%
See 1 more Smart Citation
“…Step 2 -computation of EPC: PBZ plasma clearance has been measured by many authors; mean reported values range from 16.3 to 41.3 ml/kg/h (Soma et al 1983;Lees et al 1987;Mills et al 1996). The most conservative value is obtained by taking the highest clearance value, i.e.…”
Section: An Example: Computational Steps For the Determination Of An mentioning
confidence: 99%
“…The most conservative value is obtained by taking the highest clearance value, i.e. 41.3 ml/kg/h (Mills et al 1996) or 991 ml/kg/24 h. Using equation 7: EPC = 4400 µg/kg/24 h = 4.44 µg/ml (7) 991 ml/kg/24 h This EPC is consistent with the EC 5 0 , which was directly determined by Toutain et al (1994) using a PK/PD approach in horses subjected to experimental arthritis (EC 5 0 from 1.5 to 4.3 µg/ml depending on the pharmacodynamic endpoint). Lees e t al.…”
Section: An Example: Computational Steps For the Determination Of An mentioning
confidence: 99%
“…The production of muscle inflammation by the injection of Freud’s adjuvant did not affect the plasma kinetics and when administered 5 weeks apart there was no within horse variability indicating that the administration of PBZ did not affect the plasma kinetics of subsequent doses (Mills et al. , 1996).…”
Section: Induced Lameness Modelsmentioning
confidence: 99%
“…The production of muscle inflammation by the injection of Freud's adjuvant did not affect the plasma kinetics and when administered 5 weeks apart there was no within horse variability indicating that the administration of PBZ did not affect the plasma kinetics of subsequent doses (Mills et al, 1996). This was verified by clinical observations that the plasma concentrations in a large population of horses were consistent postrace when a routine administration schedule was established in a horse and previous administrations did not affect subsequent doses.…”
Section: Induced Lameness Modelsmentioning
confidence: 99%
“…A fenilbutazona é usada por sua atividade antiinflamatória, analgésica e antipirética no tratamento de várias formas de claudicação (Booth e McDonald, 1992). É administrada com doses entre 2,2 e 8,8mg/kg, porém a dose de 4,4mg/kg é a mais utilizada em equinos (Mills et al, 1996). Esse anti-inflamatório inibe a atividade da cicloxigenase e a subsequente atividade de conversão de ácido araquidônico em metabólitos de prostaglandina (Hinchcliff, 1995).…”
Section: Introductionunclassified